Nutritional Cues Control Pseudomonas aeruginosa Multicellular Behavior in Cystic Fibrosis Sputum - Palmer, Kelli L. (American Society for Microbiology (ASM), 2007)
The sputum (mucus) layer of the cystic fibrosis (CF) lung is a complex substrate that provides Pseudomonas aeruginosa with carbon and energy to support high-density growth during chronic colonization. Unfortunately, the CF lung sputum layer has been difficult to mimic in animal models of CF disease, and mechanistic studies of P. aeruginosa physiology during growth in CF sputum are hampered by its complexity. In this study, we performed chromatographic and enzymatic analyses of CF sputum to develop a defined, synthetic CF sputum medium (SCFM) that mimics the nutritional composition of CF sputum. Importantly, P. aeruginosa displays similar phenotypes during growth in CF sputum and in SCFM, including similar growth rates, gene expression profiles, carbon substrate preferences, and cell-cell signaling profiles. Using SCFM, we provide evidence that aromatic amino acids serve as nutritional cues that influence cell-cell signaling and antimicrobial activity of P. aeruginosa during growth in CF sputum.